Discovery, Biocatalytic Exploration and Structural Analysis of a 4‐Ethylphenol Oxidase from Gulosibacter chungangensis. (30th September 2021) - Alvigini, Laura; Gran‐Scheuch, Alejandro; Guo, Yiming; Trajkovic, Milos; Saifuddin, Mohammad; Fraaije, Marco W.; Mattevi, Andrea
Abstract: The vanillyl‐alcohol oxidase (VAO) family is a rich source of biocatalysts for the oxidative bioconversion of phenolic compounds. Through genome mining and sequence comparisons, we found that several family members lack a generally conserved catalytic aspartate. This finding led us to study a VAO‐homolog featuring a glutamate residue in place of the common aspartate. This 4‐ethylphenol oxidase from Gulosibacter chungangensis (Gc4EO) shares 42 % sequence identity with VAO from Penicillium simplicissimum, contains the same 8α‐N 3 ‐histidyl‐bound FAD and uses oxygen as electron acceptor. However, Gc4EO features a distinct substrate scope and product specificity as it is primarily effective in the dehydrogenation of para ‐substituted phenols with little generation of hydroxylated products. The three‐dimensional structure shows that the characteristic glutamate side chain creates a closely packed environment that may limit water accessibility and thereby protect from hydroxylation. With its high thermal stability, well defined structural properties and high expression yields, Gc4EO may become a catalyst of choice for the specific dehydrogenation of phenolic compounds bearing small substituents. Abstract : Gc4EO, a new member of the VAO/PCMH family from the actinobacteria Gulosibacter chungangensis was discovered. This oxidase is a very appealing biocatalyst for the oxidation of 4‐alkylphenols, exhibiting high conversion yields with an attractive chemoselectivity towards the production of alkenes. Gc4EO showed high activity to produce 4‐vinylphenol, an interesting building block for the synthesis of polyvinylphenol.